Analysing The Effects of Ethical Attitude Levels of Consumers towards The Customers’ Reactions to Other Customers’ Misbehaviour - Kop, Aysegul Eda (2013)
The misbehaviours of consumers become a serious problem in the market. Although the companies try to take security precautions and some of these methods help to decrease the incidents, the problems have not solved yet. In addition to the precautions of companies, the reactions of consumers have a major impact on misbehaviours in society. As a result, it is stated in many previous researches that people are more accustomed to misbehaviours according to last decades. That means misbehaviours become a part of daily life, although they disturb social interactions. The issue that this study addresses is the lack of research that is examining the relationship between the ethical levels of consumers and their reactions to misbehaviours. To address this problem, the purpose of the study will be exploring ethical levels of consumers and their possible reactions to some kinds of misbehaviours. To achieve this, an online questionnaire was conducted during one week and 93 consumers participated to the survey. The data of questionnaires were analysed with some statistical methods. The classifications of ethical levels of consumers and their reactions to misbehaviours helped to the researcher to examine the relationship among them. The data that is collected in this research did not lead to the appropriate results that support the literature review. A different sampling may change the results.